Flexible anti-icing composite film with force and damage perception and preparation method thereof
By adopting a flexible composite film with a layered structure in the anti-icing film, combining the PDMS thermal insulation layer and hydrophobic modified particles, the problems of heat loss and ineffective heating are solved, and surface damage monitoring is achieved through carbon nanotubes, achieving all-weather anti-icing performance and sensitive force and damage sensing functions.
Patent Information
- Application Number
- CN202510073409.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-17
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-01-17
AI Technical Summary
The existing anti-icing films have problems of heat loss and ineffective heating under low temperature conditions, as well as the problem of difficulty in achieving surface deformation and damage monitoring of membranes.
A flexible composite film with a layered structure is used, the bottom layer is a PDMS thermal insulation layer, which contains artificially controlled bubbles, and the top layer is hydrophobic modified particles, which are prepared by spraying. This film not only has photothermal, electric and superhydrophobic properties, but also enables surface damage monitoring through conductive paths formed by carbon nanotubes.
It effectively reduces heat loss, prevents ineffective heating of the substrate, achieves all-weather anti-icing performance, and has sensitive force and damage sensing functions, which can timely monitor and prevent surface damage.
Smart Images

Figure CN119875182A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of anti-icing materials, and in particular to a flexible anti-icing composite film with force and damage perception and a preparation method thereof. Background Art
[0002] When wind turbine blades, aircraft wings and other equipment are running in a low-temperature environment, surface frost and ice will occur. On the one hand, it will increase the overall weight of the equipment. On the other hand, long-term ice on the surface will damage the equipment and cause equipment failure. At present, the most common deicing methods include spraying chemical deicers and mechanical deicing. In order to save manpower and material resources, many studies focus on surface anti-icing technology to delay or even prevent surface icing. Such technologies include super-hydrophobic surfaces and photothermal surfaces. Super-hydrophobic surfaces reduce or even prevent contact with water droplets through their unique water-repellent effect, thereby delaying surface icing. However, since the surface energy of the surface will increase under low temperature conditions, its water repellency will decrease, the contact angle of water droplets on the surface will continue to decrease, and the contact area with the surface will continue to increase, resulting in enhanced heat transfer and accelerated icing. Although many related super-hydrophobic surfaces are constantly improved, in the final analysis, they cannot prevent the contact between the surface and water droplets, or even prevent the increase of contact area at low temperatures, and cannot completely block heat transfer, and cannot prevent the surface water droplets from freezing. They can only delay icing to a certain extent. Therefore, it can only be used as an auxiliary anti-icing means. The advantage of photothermal surfaces is that they can achieve photothermal conversion under sunlight, automatically heating the surface to above the freezing point of water to prevent the surface from freezing. The surface performs well under light conditions, but will fail in dark conditions. Some studies have combined the two technologies to prepare composite functional surfaces that have both photothermal and super-hydrophobic properties. Some surfaces also have electrothermal properties, which can achieve all-weather anti-icing and maximize energy savings.
[0003] Although the surface with added electrothermal properties has all-weather anti-icing performance, the heat generated by its photothermal or electrothermal properties is easily dissipated through the substrate, and even accumulated near the substrate, which leads to the need to achieve heat loss on the anti-icing surface, and at the same time leads to ineffective heating of the substrate. The photothermal and especially electrothermal effects of many similar surfaces usually cause the surface to rise to extremely high temperatures to improve the efficiency of anti-icing and ice melting, but this also causes the heat dissipated from the surface to heat the substrate, causing unnecessary ineffective heating. For temperature-sensitive devices, this ineffective heating can lead to adverse consequences such as damage. There is currently no perfect solution to the problem of heat loss and ineffective heating. Another problem is that whether it is a super-hydrophobic surface or a photothermal and electrothermal surface, the surface is damaged by external forces, which will weaken its anti-icing effect or even make it ineffective. If long-term failure is not discovered in time, it will lead to various adverse consequences. Therefore, it is also necessary to monitor the external forces and damages on the surface in real time, but there is no good solution for this type of surface in the prior art. Summary of the invention
[0004] In order to solve the problems of heat loss and ineffective heating on the surface of the anti-icing film in the prior art, as well as the difficulty in monitoring deformation and damage of the film surface, the present invention provides a flexible anti-icing composite film with force and damage perception and a preparation method thereof.
[0005] The flexible anti-icing composite film with force and damage perception provided by the present invention is prepared by the following method:
[0006] S1, preparing PDMS thermal insulation bottom layer;
[0007] Mix polydimethylsiloxane (PDMS), a curing agent and hollow silica particles, then add n-hexane to dilute, mix and stir evenly, pour the mixture into a mold, heat it to semi-solidify it, and obtain a PDMS thermal insulation bottom layer;
[0008] S2, preparing hydrophobically modified particles;
[0009] Add perfluorodecyltrimethoxysilane, deionized water, carbon nanotubes and carbon black particles into n-hexane, heat and stir at 50-70° C. for 1-2 hours, and then dry at 60° C. for 1 hour to obtain hydrophobically modified particles;
[0010] S3. Preparation of PDMS-coated modified particles:
[0011] The hydrophobic modified particles obtained in step S2 are diluted with n-hexane, and then polydimethylsiloxane and a curing agent are added, and stirred at room temperature for 20 minutes to obtain a dispersion of PDMS-coated modified particles;
[0012] S4, preparing a composite membrane;
[0013] The dispersion obtained in step S3 is uniformly sprayed onto the PDMS thermal insulation base layer obtained in step S1 through a spray gun, and heated and cured to obtain a composite film with photothermal, electrothermal and super-hydrophobic properties, that is, a flexible anti-icing composite film.
[0014] The particle size of the hollow silicon dioxide particles is 1-3 μm, and the amount of the hollow silicon dioxide particles accounts for 8% of the mass of the polydimethylsiloxane.
[0015] Preferably, in step S1, the heating temperature is 100°C and the curing time is several minutes, preferably 8 minutes.
[0016] Preferably, the inner diameter of the carbon nanotube is 3-5 nm, the outer diameter is 8-15 nm, and the length is 3-12 μm; and the particle size of the carbon black particles is 23-28 nm.
[0017] Preferably, in step S3, the amount of the hydrophobically modified particles is 16% of the mass of the polydimethylsiloxane.
[0018] Preferably, in step S4, the caliber of the spray gun is 0.5 mm, the spraying distance is 15 cm, the spraying time is 2-3 s, the curing temperature is 60° C., and the curing time is 4 h.
[0019] Compared with the prior art, the present invention is beneficial in that:
[0020] (1) In order to solve the problem of heat loss and ineffective heating on the membrane surface, the present invention is inspired by the fat layer of the skin and prepares a flexible composite membrane with a layered structure. The bottom layer of the membrane is a PDMS layer, which contains artificially controlled bubbles. The thermal conductivity of gas is lower than that of solid. The storage of bubbles in the solid can effectively reduce the overall heat conduction of the substrate to enhance the thermal insulation effect. The thermal insulation effect is effectively enhanced by regulating the distribution of bubbles in PDMS, and the control of bubbles does not require complex means. It only needs to utilize the tiny bubbles naturally generated by PDMS during the stirring process to achieve different bubble distribution and size regulation at different temperatures and diluent contents. The prepared composite membrane has excellent thermal insulation performance. The bottom layer of the composite membrane can insulate well and prevent the heat generated by the top coating from being conducted to the substrate below. On the one hand, it can preserve heat to prevent excessive loss, and on the other hand, it can prevent excessive heating of the substrate. When the temperature of the photothermal surface reaches a high temperature of 91.7°C, the back side is only maintained at around 55°C, which has an excellent thermal insulation effect.
[0021] (2) In order to enhance the tensile strength of the film or coating and avoid the conflict between the mechanical strength of the film and other functions, the present invention is inspired by the layered structure of the skin and divides the film into two layers according to its function, wherein the main functional layer for achieving anti-icing is located in the upper layer, and the lower layer is an auxiliary functional layer for providing toughness and heat insulation for the film. This layered structure is interconnected by PDMS to form an integral body, and the bonding strength between the two layers is excellent, which takes into account the various properties required for the anti-icing flexible film to the greatest extent.
[0022] (3) Damage to the super-hydrophobic or photothermal surface can lead to functional failure and cause adverse consequences. In order to meet the needs of preventing and monitoring membrane surface damage, the present invention realizes the monitoring of surface deformation and damage through the conductive path formed by carbon nanotubes in the coating. After the surface is subjected to external pressure or damage, the flexible PDMS in the bottom insulation layer of the surface and the bubbles therein can enhance the deformation of the top coating. Under the action of very small external force, a certain deformation can be produced, and it has a high monitoring sensitivity, that is, it has sensitive force and damage perception function. The composite membrane can well monitor the pressure, bending deformation and damage applied to its surface, and can provide an effective means for the prevention and monitoring of surface damage, and prevent various problems caused by membrane surface failure.
[0023] (4) The composite film of the present invention has excellent photothermal conversion properties and electrothermal properties. Under the normal light intensity of 1 sun, the surface temperature of the film surface can be increased by about 31°C compared with the ambient temperature, with good photothermal conversion efficiency, and can heat the surface well under daytime light conditions to prevent the surface from freezing. Under a constant voltage of 15V, the surface temperature of the composite film can be increased by about 86°C compared with the ambient temperature, with excellent electrothermal performance.
[0024] In summary, the composite membrane surface has super-hydrophobicity, photothermal and electrothermal properties, that is, it has excellent anti-icing performance, and is expected to achieve all-weather surface anti-icing in various environments. Moreover, the preparation method of the composite membrane is simple and easy. The double-layer integrated structure of the composite membrane is achieved by automatically connecting the PDMS in the upper and lower layers, without the need for additional tedious steps; the top coating adopts the spraying method, which is simpler than the dip coating method.
[0025] Other advantages, objectives and features of the present invention will be embodied in part through the following description, and in part will be understood by those skilled in the art through study and practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 Surface and cross-sectional morphology images of the composite film of Example 1, wherein (a) is a surface image and (b) is a cross-sectional image.
[0027] Figure 2 This is a photothermal effect diagram of the composite film of Example 1.
[0028] Figure 3 This is a temperature difference diagram between the front and back sides of the composite film under light and power conditions.
[0029] Figure 4 This is the experimental result of the electrothermal effect of the composite film at a voltage of 15V.
[0030] Figure 5 These are the results of force and damage perception tests, where (a) is the current change diagram of the composite film under different pressing stimuli; (b) is the current change diagram of the composite film after surface damage.
[0031] Figure 6 The figures are the results of anti-icing experiments, where (a) is the glass surface film of Comparative Example 1; (b) is the aluminum plate surface film of Comparative Example 2; and (c) is the composite film of Example 1. DETAILED DESCRIPTION
[0032] The preferred embodiments of the present invention are described below in conjunction with the accompanying drawings. It should be understood that the preferred embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.
[0033] Example 1
[0034] A method for preparing a flexible anti-icing composite film with force and damage sensing:
[0035] S1. Prepare PDMS thermal insulation bottom layer: Mix 5g of PDMS, 0.5g of curing agent and 0.4g of hollow silica particles, and then add 20ml of n-hexane to dilute. Stir the mixture on a magnetic stirrer at 3000r / min for 20min. Finally, pour the mixture into a mold, which is a circular steel ring with a diameter of 3cm and a thickness of 2mm; then heat it at 100℃ for 8min to semi-cured and formed it to obtain a PDMS thermal insulation bottom layer.
[0036] S2. Preparation of hydrophobically modified particles: Add 1 ml of perfluorodecyltrimethoxysilane, 500 μl of deionized water, 400 mg of carbon nanotubes and 400 mg of carbon black particles to 20 ml of n-hexane, heat and stir at 60° C. for 2 h in an oil bath stirrer, and then dry at 60° C. for 1 h to obtain hydrophobically modified particles.
[0037] S3. Preparation of PDMS-coated modified particles: The modified particles obtained in step S2 were diluted with 20 ml of n-hexane, followed by addition of 5 g of PDMS and 0.5 g of a curing agent, and stirred at room temperature (20-25° C.) for 20 min to obtain a dispersion of PDMS-coated modified particles.
[0038] S4. Preparation of composite membrane: The particle dispersion obtained in step S3 is uniformly sprayed onto the PDMS thermal insulation base layer obtained in step S1 through a 0.5 mm caliber spray gun at a pressure of 0.3 MPa, and the double-layer membrane sprayed with the coating is cured at 60° C. for 4 h to obtain a composite membrane with photothermal, electrothermal and super-hydrophobic properties, i.e., a flexible anti-icing composite membrane.
[0039] The curing agent is SYLGARD 184 silicone rubber curing agent. The curing agent used in subsequent comparative examples 1 and 2 is the same.
[0040] The surface and cross-sectional micromorphology of the composite membrane are shown in Figure 1 , where (a) is the surface view and (b) is the cross-sectional view.
[0041] Comparative Example 1
[0042] A method for preparing a single-layer film:
[0043] (1) Preparation of hydrophobically modified particles: 1 ml of perfluorodecyltrimethoxysilane, 500 μl of deionized water, 400 mg of carbon nanotubes and 400 mg of carbon black particles were added to 20 ml of n-hexane, heated and stirred at 60° C. for 2 h in an oil bath stirrer, and then dried at 60° C. for 1 h to obtain hydrophobically modified particles.
[0044] (2) Preparation of PDMS-coated modified particles: The modified particles obtained in step (1) were diluted with 20 ml of n-hexane, followed by the addition of 5 g of PDMS and 0.5 g of a curing agent, and stirred at room temperature (20-25° C.) for 20 min to obtain a PDMS-coated modified particle dispersion.
[0045] (3) Preparation of a glass monolayer film: The particle dispersion obtained in step (2) was evenly sprayed onto a 2 mm thick glass plate using a 0.5 mm caliber spray gun at a pressure of 0.3 MPa, and the monolayer film was cured at 60° C. for 4 h to obtain a monolayer film as a control group.
[0046] Comparative Example 2
[0047] A method for preparing a single-layer film:
[0048] (1) Preparation of hydrophobically modified particles: 1 ml of perfluorodecyltrimethoxysilane, 500 μl of deionized water, 400 mg of carbon nanotubes and 400 mg of carbon black particles were added to 20 ml of n-hexane, heated and stirred at 60° C. for 2 h in an oil bath stirrer, and then dried at 60° C. for 1 h to obtain hydrophobically modified particles.
[0049] (2) Preparation of PDMS-coated modified particles: The modified particles obtained in step (1) were diluted with 20 ml of n-hexane, followed by addition of 5 g of PDMS and 0.5 g of a curing agent, and stirred at room temperature (20-25° C.) for 20 min to obtain a PDMS-coated modified particle dispersion.
[0050] (3) Preparation of a single-layer film on an aluminum plate: The particle dispersion obtained in step (2) was evenly sprayed onto a 2 mm thick aluminum plate using a 0.5 mm caliber spray gun at a pressure of 0.3 MPa, and the single-layer film was cured at 60° C. for 4 h to obtain a single-layer film as a control group.
[0051] The double-layer composite film and the single-layer film prepared in Example 1 and Comparative Examples 1 and 2 were subjected to a light-to-heat conversion test, an electrothermal test, a force (damage) perception test, and an anti-icing test. The test process is as follows:
[0052] (1) Photothermal conversion experiment:
[0053] The double-layer composite film and the single-layer film prepared in Example 1, Comparative Examples 1 and 2 were placed on a constant temperature physical and chemical plate, and the surface was irradiated with a light intensity of 1 sun for 300 seconds. The final temperature rise of each sample surface was recorded by an infrared thermal imager. The experimental results are shown in Figure 2 It can be seen that compared with the single-layer film on the aluminum plate and the glass substrate, the double-layer film with the PDMS insulation substrate has a more obvious surface temperature rise, and the temperature difference can reach 31°C compared with the surrounding environment, while the temperature difference of the single-layer film on the glass plate is 16.4°C, and the temperature difference of the single-layer film on the aluminum plate is only 12.8°C. At the same time, the temperature difference between the front and back sides of the composite film of Example 1 was measured, and the results are shown in Figure 3 When the membrane surface temperature reaches 57.7°C, the temperature difference between the front and back sides reaches 20.1°C, and when the surface temperature reaches 91.7°C, the temperature difference reaches 36°C. The above results prove the excellent thermal insulation performance of PDMS thermal insulation substrate.
[0054] (2) Electric heating test:
[0055] The composite film prepared in Example 1 was used as the experimental object. The positive and negative electrodes of the power supply were clamped at both ends of the composite film, and a constant voltage of 15V was applied. The temperature of the sample surface at different times was recorded by an infrared thermal imager. The test results are shown in Figure 4 The test results show that the surface temperature of the composite film can rise by about 86°C within 300s, which shows an excellent electrothermal effect.
[0056] (3) Force and damage perception test:
[0057] The composite film prepared in Example 1 was taken as the experimental object. The surface of the film was connected to the positive and negative electrodes of the electrochemical workstation through copper wires. A constant voltage of about 10 V was applied. After the surface current was stable, different external pressures were applied to the surface to observe and record the changes in the surface current. The coating was scratched by a sharp object to observe the changes in the surface current. The results are shown in Table 1. Figure 5 . (a) is the current change diagram of the composite film under different pressure stimulation; (b) is the current change diagram of the composite film after the surface is damaged. The results show that the composite film surface can well monitor the external force and damage on the surface, with high sensitivity.
[0058] (4) Anti-icing test:
[0059] Take the double-layer composite film and the single-layer film prepared in Example 1, Comparative Examples 1 and 2, place the samples on a semiconductor cold stage, drop 10 μl of water on the surface of the three samples, then lower the temperature of the cold stage to -15°C, perform a surface water droplet freezing test at -15°C and 60% relative humidity, shoot the freezing process of the water droplets with a high-speed camera, and record the freezing time of the surface water droplets. The experimental results are shown in Figure 6 . (a) is the anti-icing test result of the glass surface film of comparative example 1; (b) is the anti-icing test result of the aluminum plate surface film of comparative example 2; (c) is the anti-icing test result of the composite film surface film of embodiment 1. The results show that the freezing time of water droplets on the glass and aluminum plate surfaces is 45s-215s, while the freezing time of the composite film surface can be extended to 1980s, which has extremely excellent anti-icing performance.
[0060] The above description is only a preferred embodiment of the present invention and does not constitute any form of limitation to the present invention. Although the present invention has been disclosed as a preferred embodiment as above, it is not intended to limit the present invention. Any technician familiar with the profession can make some changes or modifications to equivalent embodiments of equivalent changes using the technical contents disclosed above without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent change and modification made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention still falls within the scope of the technical solution of the present invention.
Claims
1. A method for preparing a flexible anti-icing composite film with force and damage sensing, characterized in that: The following steps are involved: S1, preparing PDMS thermal insulation bottom layer; The polydimethylsiloxane, curing agent and hollow silica particles are mixed, and then n-hexane is added to dilute and mix and stir evenly, and the mixture is poured into a mold and heated to semi-cured to obtain a PDMS thermal insulation bottom layer; S2, preparing hydrophobically modified particles; Add perfluorodecyltrimethoxysilane, deionized water, carbon nanotubes and carbon black particles into n-hexane, heat and stir at 50-70° C. for 1-2 hours, and then dry to obtain hydrophobically modified particles; S3. Preparation of PDMS-coated modified particles: The hydrophobic modified particles obtained in step S2 are diluted with n-hexane, and then polydimethylsiloxane and a curing agent are added, and stirred at room temperature for 20 minutes to obtain a dispersion of PDMS-coated modified particles; S4, preparing a composite membrane; The dispersion obtained in step S3 is uniformly sprayed onto the PDMS thermal insulation base layer obtained in step S1 through a spray gun, and heated and cured to obtain a composite film with photothermal, electrothermal and super-hydrophobic properties, that is, a flexible anti-icing composite film.
2. The method for preparing a flexible anti-icing composite film with force and damage sensing according to claim 1, characterized in that: The particle size of the hollow silicon dioxide particles is 1-3 μm, and the amount of the hollow silicon dioxide particles accounts for 8% of the mass of the polydimethylsiloxane.
3. The method for preparing a flexible anti-icing composite film with force and damage sensing according to claim 1, characterized in that: In step S1, the heating temperature is 100°C and the curing time is several minutes.
4. The method for preparing a flexible anti-icing composite film with force and damage sensing according to claim 1, characterized in that: In step S2, the drying temperature is 60°C.
5. The method for preparing a flexible anti-icing composite film with force and damage sensing according to claim 1, characterized in that: The inner diameter of the carbon nanotube is 3-5nm, the outer diameter is 8-15nm, and the length is 3-12μm; the particle size of the carbon black particles is 23-28nm.
6. The method for preparing a flexible anti-icing composite film with force and damage sensing according to claim 1, characterized in that: In step S3, the amount of the hydrophobically modified particles is 16% of the mass of the polydimethylsiloxane.
7. The method for preparing a flexible anti-icing composite film with force and damage sensing according to claim 1, characterized in that: In step S4, the caliber of the spray gun is 0.5 mm, the spraying distance is 15 cm, the spraying time is 2-3 s, the curing temperature is 60° C., and the curing time is 4 h.
8. A flexible anti-icing composite film with force and damage sensing, characterized in that: Prepared by the preparation method according to any one of claims 1 to 7.
Citation Information
Patent Citations
Application of hydrophobic heat insulating and cooling film
CN111842072A
Electrothermal super-hydrophobic anti-icing and de-icing composite coating system as well as preparation method and application thereof
CN117986964A
Preparation method and application of polydimethylsiloxane super-hydrophobic anti-icing and deicing material
CN119286394A
Anti-icing and Anti-frosting coating composite
US20240318030A1
Sprayable silicone polymer dispersion
WO2020128773A1